A combination optimisation method for the estimation of material parameters for viscoelastic solids. (1st January 2014) - Cui, Zhiwei; Brinson, L. Catherine
In the current work, we propose a two-step optimisation method to determine the coefficients of the Prony series expansion for a viscoelastic constitutive model by combining the benefits of particle swarm optimisation and linear least square solver. The entire fitting progress is decoupled and divided into two portions. Each optimisation approach is used for obtaining one set of parameters. This method overcomes the usual difficulties of original function determinations and could find the global optimal solution with a high precision. The quality of the developed method is verified by three examples on both time-domain and frequency-domain experimental data. Simulation results are consistent with corresponding experimental data, showing that the new technique is valid and applicable for estimating structural properties of viscoelastic materials.